2005
DOI: 10.1097/01.psy.0000161201.45643.8d
|View full text |Cite
|
Sign up to set email alerts
|

Social Network and Coronary Artery Calcification in Asymptomatic Individuals

Abstract: Social network indices such as being single or widowed are associated with CAC, independent of age and coronary risk factors. Because coronary calcification has been identified as a potential marker of early atherosclerosis, these findings may partially explain the predictive value of limited social networks for future adverse cardiovascular health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 50 publications
4
42
1
1
Order By: Relevance
“…They also support behavior conducive to good health. With regard to somatic pathology, a lack of close personal relationships, reflected in being single or widowed, has been found to be associated with greater incidence of coronary artery calcification independent of age and coronary risk factors (Kop et al, 2005). Subjects with more extensive social networks have been shown to have greater antibody response to influenza vaccine (Pressman et al, 2005), and social participation and engagement have also been shown to be predictive of lesser dementia and cognitive decline in men and women who are more than 65 years of age (Kawachi & Berkman, 2001).…”
Section: Social Networkmentioning
confidence: 98%
“…They also support behavior conducive to good health. With regard to somatic pathology, a lack of close personal relationships, reflected in being single or widowed, has been found to be associated with greater incidence of coronary artery calcification independent of age and coronary risk factors (Kop et al, 2005). Subjects with more extensive social networks have been shown to have greater antibody response to influenza vaccine (Pressman et al, 2005), and social participation and engagement have also been shown to be predictive of lesser dementia and cognitive decline in men and women who are more than 65 years of age (Kawachi & Berkman, 2001).…”
Section: Social Networkmentioning
confidence: 98%
“…Correlating with human participants, research has shown that subjects with poor social support have exaggerated blood pressure and heart rate responses to stressful situations with a remarkably slow recovery time [22]. These same set of people also experience autonomic imbalances [23], exaggerated inflammation [24], increased calcification in the coronary arteries [25], and significant hypertrophy of the left ventricle [26]. These evidences support the hypothesis that social isolation contributes to CVD morbidity and mortality.…”
Section: Reviewmentioning
confidence: 99%
“…Likewise, social relationships have been linked to the development [16,17] and progression [18][19][20][21] of cardiovascular disease [22]-a leading cause of death globally. Therefore, synthesis of the current empirical evidence linking social relationships and mortality, along with clarifications of potential moderators, may be particularly relevant to public health and clinical practice for informing interventions and policies aimed at reducing risk for mortality.…”
Section: Introductionmentioning
confidence: 99%